THE ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN MEDIATING THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON HOSPITAL EMPLOYEE PERFORMANCE - Nelly Noviyanti; Tetra Hidayati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aimed to analyze and empirically prove the influence of transformational leadership on employee performance through the mediating role of Organizational Citizenship Behavior (OCB) at Bhayangkara Hospital. This research was motivated by the phenomenon of fluctuating employee performance and research gaps regarding the effectiveness of transformational leadership in various organizational contexts. This study employed a quantitative approach with a survey method. The population consisted of 300 hospital employees, with a sample of 171 respondents determined using the Slovin formula. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS software. The results showed that transformational leadership did not have a significant effect on either employee performance or the formation of OCB. Conversely, OCB was proven to have a very significant and dominant positive effect on employee performance. Due to the insignificant influence of leadership on OCB, the OCB variable was not proven to act as a mediator in the relationship between transformational leadership and performance. These findings concluded that current high employee performance was driven more by voluntary initiatives and internal employee dedication rather than by the intervention of the supervisor's leadership style